ANALISIS KONTEN CAMPAIGN TRAVELOKA #LIHATDUNIALAGI : “WASEDABOYS MASUK KE PEDALAMAN PAPUA! KETEMU SUKU DANI” PADA AKUN YOUTUBE NIHONGO MANTAPPU - Ratih Hasanah Sudrajat; Cahaya Mustika Pertiwi (Linimasa : Jurnal Ilmu Komunikasi, 2023)
Dissemination of information through campaign activities can be created with organized communication and of course it cannot be separated from conveying messages so that the contents of campaign messages can reach the public, of course they must be disseminated or published to the wider community. Submission and dissemination of information can take advantage of social media. The #Lihatdunialagi campaign created by Traveloka is an information dissemination that aims to influence the wider community to raise awareness and knowledge about cultural diversity in Indonesia, including cultural diversity in Papua. This research was made to find out how cultural diversity and the effectiveness of communication messages in Traveloka's #Lihatdunialagi campaign content with the title "Wasedaboys Enter the Interior of Papua! Meet the Dani Tribe”. The author uses a qualitative content analysis method with an interpretive paradigm. The data validity technique used is source triangulation and technique/method triangulation. The results of this study show that the content of Traveloka's #Lihatdunialagi campaign with the title "Wasedaboys Enters the Interior of Papua! Meet the Dani Tribe" contains a category of forms of cultural diversity and a form of the effectiveness of communication messages but with a different number of scores on the coding method.